2022-RA-1089-ESGO Opportunistic salpingectomy (OS) for prevention of ovarian cancer has become a de facto standard in Germany. (20th October 2022) - Kather, Angela; Vorwergk, Julia; Cruz, Jorge Jimenez; Mothes, Anke R; Beteta, Carmen C; Keller, Maren; Pölcher, Martin; Mustea, Alexander; Sehouli, Jalid; Runnebaum, Ingo B
Abstract : Introduction/Background: The most prevalent and aggressive subtype of ovarian carcinoma (high grade serous carcinoma, HGSC) originates in many cases from the fallopian tubes. Because of poor prognosis and unavailable early diagnosis of HGSC, opportunistic salpingectomy (OS) has been implemented into clinical routine in many countries. OS means complete bilateral resection of fallopian tubes with preservation of ovaries at opportunity of benign gynecological surgery such as hysterectomy. Only 13 of 130 of national partner societies of FIGO (International Federation of Obstetrics and Gynecology) published a statement on OS until recently. Methodology: (1) Survey of German gynecologists conducted by University Hospital Jena and Charité-Universitätsmedizin Berlin in cooperation with NOGGO e.V. and AGO e.V. (2) Retrieval of case numbers for years 2005–2020 from Federal Statistical Office of Germany (Destatis). Results: (1) Survey: Most respondents (92%) perform OS in benign hysterectomy for risk-reduction of malignant (96%) and benign (47%) disease. Recommendation of OS for all women with completed family planning at opportunity of benign pelvic surgery was approved by 68%. (2) In 2020 (50.398 cases) four times more cases of salpingectomy were coded by German public hospitals compared to 2005 (12.286 cases). Of all hysterectomies conducted in 2020, about 45% and in the age group of 35- to 49-year-old women 65%, were combined with salpingectomy. Salpingectomies in 2020 were coded in 67% of cases in combination with a benign indication for hysterectomy and in only 11% with indications of tubal pathologies. (Runnebaum et al., 2022) Conclusion: OS is broadly accepted and performed by German gynecologists. Expert consensus statements of national and international gynecologic societies appear to be due.